Microbiological quality (yeast and mold) of dried fruits in Kabul, Afghanistan: A laboratory study - Murtaza Jafari; Maryam moetamedi (Global Scientific Publishing, 2022)
Food safety is one of the most important issues in the world. Consumption of healthy food products leads to improvement in major functions in the body. Dried fruits are one of the most widely consumed food products in Afghanistan, and millions of tons of these products are still exported annually. Objectives and Methods: The aim of this study was to evaluate fungal contamination in dried fruits in food markets in Kabul. This study is an experimental study conducted in NEI laboratories on 14 samples of dried fruits in food markets in Kabul. Results: In this study, more than 14 samples of dried fruits available in food markets in Kabul, in NEI laboratories from December 6, 2020 to April 20, 2021, only one of these samples was free of any fungal contamination, 4 samples Less than 100 CFUs, 6 samples between 100 and 200 CFUs, and only 3 specimens with more than 200 CFUs were infected with the fungus (yeast and mold).
Keywords: Dried fruits; Yeast and Mold Contamination; fungal; contamination